Benchmarking the complex geometric profiles, dimensional accuracy and surface analysis of printed parts. Issue 2 (17th October 2019) - Subbaian Kaliamoorthy, Paridhi; Subbiah, Rajkumar; Bensingh, Joseph; Kader, Abdul; Nayak, Sanjay
Abstract : Purpose: Additive manufacturing has paved a way for geometrical freedom and mass customization of new and innovative products. However, it has a few limitations in printing complex geometries and sizes. The purpose of this paper is three-dimensional printing of metal parts using selective laser melting (SLM) has several intricacies. Design/methodology/approach: To test the capabilities of SLM, the complex geometries of varying sizes, orientations, shapes such as square and cylindrical features, thin wall structures and holes were checked for dimensional accuracy and surface roughness. Findings: The outcome of the study represents the capabilities of SLM and provide insight for solving the technological issues and processing constraint in the manufacture of metal parts from aluminum alloy. The analysis has proven that there is significant accuracy in dimension for large features in comparison with smaller one. The dimensional reproducibility was determined with the aid of an optical measuring system and the range of errors were calculated. These results show that the dimensional accuracy of the features in the printed part was within acceptable tolerance limits. This paper also investigated the significant contributing factors influencing printing of two and three-dimensional surface roughness based on the result of surface profilometer and it was observed that the surface was smoothened with the presence of overhangs and supports. Originality/value: The ability of SLM to fabricate conformer cooling channels to support mould fabrication was tested. From the experimental result, it was observed that the quality of printing of conformal cooling channels depended on the diameter of channels with larger distortions in the channel having smaller diameter. The innovative aspect of the work was the study of build orientation combined with the investigated material.